2015
DOI: 10.1371/journal.pone.0131275
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sleep Is an Evolutionarily Adaptive Response to Starvation Stress in Drosophila

Abstract: Animals maximize fitness by modulating sleep and foraging strategies in response to changes in nutrient availability. Wild populations of the fruit fly, Drosophila melanogaster, display highly variable levels of starvation and desiccation resistance that differ in accordance with geographic location, nutrient availability, and evolutionary history. Further, flies potently modulate sleep in response to changes in food availability, and selection for starvation resistance enhances sleep, revealing strong genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 42 publications
1
59
0
Order By: Relevance
“…For example, Drosophila has been reported to show lower locomotor activity under prolonged nutritionally adverse conditions (Rion and Kawecki, 2007;Slocumb et al, 2015). Inner-nest workers did indeed show a reduction in foraging activity during the first 3 weeks of the experiment, supporting this hypothesis in our study.…”
Section: Discussionsupporting
confidence: 87%
“…For example, Drosophila has been reported to show lower locomotor activity under prolonged nutritionally adverse conditions (Rion and Kawecki, 2007;Slocumb et al, 2015). Inner-nest workers did indeed show a reduction in foraging activity during the first 3 weeks of the experiment, supporting this hypothesis in our study.…”
Section: Discussionsupporting
confidence: 87%
“…In the next stage of this investigation, we examined three long‐term selected populations of desiccation resistant flies (DR populations A, B, and C) obtained through artificial selection through about 200 generations (Slocumb et al, ) (also provided by Dr. Allen G. Gibbs). We observed a significant reduction in the number of ABLKs in two of the three populations.…”
Section: Resultsmentioning
confidence: 99%
“…For 519 instance, Schwasinger- Schmidt et al (2012) found that activity of flies with high starvation 520 resistance was reduced following 15 generations of selection for starvation resistance in both 521 males and females. Slocumb et al (2015) also found that waking activity was reduced in lines 522 selected to have high starvation resistance. Although previous associations between increased 523 starvation tolerance and lower activity levels, metabolic rate, and changes in behavior have been 524 observed (Murphey and Hall 1969;Hoffmann and Parsons 1989a;Blows and Hoffman 1993; and starvation resistance may be genetically correlated Rose et al 1992;536 Chippindale et al 1996;Harshman et al 1999;Schwasinger-Schmidt et al 2012;Slocumb et al 537 2015).…”
mentioning
confidence: 92%
“…A more intensive sampling of the DSPR would be necessary to thoroughly 483 investigate the genetic correlation between starvation and desiccation resistance. One physiological mechanism that may increase tolerance to environmental stressors is 493 a reduction in metabolic rate (Lighton and Bartholomew 1988;Hoffmann and Parsons 1989a;b, 494 1991;Chippindale et al 1996;Djawdan et al 1997;Marron et al 2003;Rion and Kawecki 2007;495 Schwasinger -Schmidt et al 2012;Slocumb et al 2015). Indeed, selection for both starvation and 496 desiccation resistance has been shown to lead to a correlated change in activity level, an indirect 497 proxy for metabolic rate Parsons 1989b, 1993;Schwasinger-Schmidt et al 2012).…”
mentioning
confidence: 99%